Comparison of Soil Phosphorus Tests for Assessing Plant Availability of Phosphorus in an Ultisol Amended with Water-Soluble and Phosphate Rock Sources. (2010) - Gikonyo, E. W.; Zaharah, A. R.; Hanafi, M. M.; Anuar, A. R.
Abstract : The effectiveness of different soil tests in assessing soil phosphorus (P) in soils amended with phosphate rocks (PRs) is uncertain. We evaluated the effects of triple superphosphate (TSP) and PRs on extractable P by conventional soil tests (Mehlich 3 [Meh3] and Bray-1 [B1]) and a nonconventional test (iron oxide–impregnated paper, strip). Extracted amounts of P were in the order: Meh3 >B1 > strip. All the tests were significantly correlated ( p = 0.001). Acidic reagents extracted more P from TSP than PRs, while the strip removed equal amounts from the two sources. The P removed by the three tests was related significantly to dry matter yield (DMY), but only in the first harvest, except for B1. Established critical P levels (CPLs) differed for TSP and PRs. In PR-fertilized soils, CPLs were 27, 17, and 12 mg P kg -1 soil for Meh3, B1, and strip, respectively, and 42, 31, and 12 mg P kg -1 soil, respectively, in TSP-fertilized soils. Thus, the strip resulted in a common CPL for TSP and PRs (12 mg P kg -1 soil). This method can be used effectively in soils where integrated nutrient sources have been used, but there is need to establish CPLs for different crops. For cost-effective fertilizer P recommendations based on conventional soil tests, there is a need to conduct separate calibrations for TSP- and PR-fertilized soils.